Background and Proposed Design for a Metformin Abdominal Aortic Aneurysm Suppression Trial - Ronald L Dalman (Radcliffe Medical Media, 2020)
Abdominal aortic aneurysm (AAA) may lead to rupture and death if left untreated. While endovascular or surgical repair is generally recommended for AAA greater than 5–5.5 cm, the vast majority of aneurysms detected by screening modalities are smaller than this threshold. Once discovered, there would be a significant potential benefit in suppressing the growth of these small aneurysms in order to obviate the need for repair and mitigate rupture risk. Patients with diabetes, in particular those taking the oral hypoglycaemic medication metformin, have been shown to have lower incidence, growth rate, and rupture risk of AAA. Metformin therefore represents a widely available, non-toxic, potential inhibitor of AAA growth, but thus far no prospective clinical studies have evaluated this. Here, we present the background, rationale, and design for a randomised, double-blind, placebo-controlled clinical trial of metformin for growth suppression in patients with small AAA.